Illnesses and Injuries at Nature Preschools. Issue 8 (October 2019) - Frenkel, Hannah; Tandon, Pooja; Frumkin, Howard; Vander Stoep, Ann
Nature preschools, where children spend the entire school day outdoors, are increasingly popular, but their health consequences have not been well researched. This study tested the hypothesis that nature preschools and conventional preschools differ in their illness and injury incidence, by comparing observed illness and injury occurrence in the two types of schools. For 14 weeks, teachers at five nature preschools and four conventional preschools in Seattle, Washington logged absences due to illness. Two nature preschools and three conventional preschools also logged injuries that occurred during the school day. There was no difference in illness incidence by preschool type, and no serious injuries were reported in either setting. Overall, the study found that nature preschools are a healthy and safe child-care model.